Development and Validation of a Risk Score for Predicting Post-acute Myocardial Infarction Infection in Patients Undergoing Percutaneous Coronary Intervention: Study Protocol for an Observational Study - Liu, Yuanhui; Wang, Litao; Lin, Yaowang; Chen, Wei; Xu, Zhengrong; Chen, Pengyuan; Dai, Yining; Zeng, Lihuan; Fan, Hualin; Xue, Ling; Chen, Jiyan; Tan, Ning; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Post-acute myocardial infarction (post-AMI) infection is an infrequent but important and serious complication in patients with ST-segment elevation myocardial infarction (STEMI) treated with percutaneous coronary intervention (PCI). Predicting its occurrence is essential for future prevention. However, little is known about the prediction of post-AMI infection in such patients to date. This study aims to develop and validate a new risk score based on risk factors for early prediction of infection in STEMI patients undergoing PCI. Methods: This prospective, multi-center and observational study assesses the predictive value of risk score for post-AMI infection among a cohort of patients hospitalized due to STEMI. The STEMI patients undergoing PCI enrolled between January 1st 2010 and May 31st 2016 were served as a development cohort while those enrolled from June 1st 2016 to May 31st 2018 were served as validation cohort. The primary endpoint was post-AMI infection during hospitalization, defined as infection requiring antibiotics (reflecting the clinical influence of infection compatible with the necessity for additional treatment), and all-cause death and major adverse cardiovascular events (MACE) including all-cause death, recurrent myocardial infarction, target vessel revascularization, and stroke were considered as secondary endpoints. The risk score model based on risk factors was established using stepwise logistic regression, and will be validated in other centers and external patients with non-ST-elevation acute coronary syndrome (NSTE-ACS). Results: This study will provide evidence on prognostic property, reliability of scoring, comparative performance, and suitability of the novel model for screening purpose in order to be recommended for clinical practice. Discussion: Our study is designed to develop and validate a clinical risk score for predicting infection in participants with STEMI who have undergone PCI. This simple tool may therefore improve evaluation of post-AMI infection and enhance future researches into the best practices to prevent or reduce infection in such patients.